Tacrolimus pharmacogenetics: the influence of genetic polymorphisms of CYP3A5, MDRl and Pregnane X Receptor (PXR) in transplant patients / Professor Dr. Mohd Zaki Salleh and Associate Prof. Dr Teh Lay Kek - Salleh, Mohd Zaki; Teh, Lay Kek (Research Management Institute (RMI), 2010)
Tacrolimus is an immunosuppressant commonly used for long term in transplant patients to prevent organ rejection. Its use faces clinical challenges in achieving optimum dose for all patients. There are wide variation in doses of tacrolimus required for patients resulting in different drug levels and unpredictable drug responses. Certain patients are predisposed to an increased susceptibility to acute rejection while many are at risk of adverse effects of tacrolimus. Tacrolimus is a substrate for both P-glycoprotein (Pgp, encoded by the gene MDR1) and CYP3A's. Differences in the intestinal P-glycoprotein and hepatic and intestinal cytochrome P4503A activities have been postulated as contributing to the wide inter-patients variations in drug levels and responses. We therefore aim to investigate the impact of the genetic polymorphism as well as expression level of MDR1 in transplant patients receiving tacrolimus.